Genetic Hearing Loss and Gene Therapy - Nathanial T Carpena; Min Young Lee (Genomics & Informatics)
Genetic hearing loss crosses almost all the categories of hearing loss which includes the following: conductive, sensory, and neural; syndromic and nonsyndromic; congenital, progressive, and adult onset; high-frequency, low-frequency, or mixed frequency; mild or profound; and recessive, dominant, or sex-linked. Genes play a role in almost half of all cases of hearing loss but effective treatment options are very limited. Genetic hearing loss is considered to be extremely genetically heterogeneous. The advancements in genomics have been instrumental to the identification of more than 6,000 causative variants in more than 150 genes causing hearing loss. Identification of genes for hearing impairment provides an increased insight into the normal development and function of cells in the auditory system. These defective genes will ultimately be important therapeutic targets. However, the auditory system is extremely complex which requires tremendous advances in gene therapy including gene vectors, routes of administration, and therapeutic approaches. This review summarizes and discusses recent advances in elucidating the genomics of genetic hearing loss and technologies aimed at developing a gene therapy that may become a treatment option for in the near future.